Problematika Penerapan Restorative Justice oleh Kejaksaan terhadap Pelaku Pencurian Residivis Non-Institusional - wira utama nugroho pamungkas (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
The Public Prosecution Service applies restorative justice in theft cases by referring to Regulation of the Attorney General Number 15 of 2020, Articles 486 and 76(1) of the former Criminal Code, and Article 23 of the new Criminal Code. Prosecutors adopt a predominantly normative approach, under which factual social aspects specifically the offender’s admission of having committed multiple thefts that were never subject to criminal responsibility or adjudicated by a final court judgment are treated as non-normative and categorized as non-institutional recidivism. As a result, restorative justice continues to be applied to such offenders. This practice generates injustice in the implementation of restorative justice, undermines justice for victims, and weakens the objectives of preventing repeat offending and restoring social balance.